Formulation, development, and characterization of loratadine emulgel - Sharaff, Chandana Setty; Renukuntla, Pranay; Peddapalli, Himabindu; Kuchukuntla, Mounika; Bakshi, Vasudha; Jadi, Rajendra Kumar (Journal of Applied Pharmaceutical Research, 2024)
Background: This study was to develop loratadine (LTD) emulgels to treat localized skin allergy. Method: Initially oil-in-water emulsion was prepared by 3 different types of surfactants & finally gelling agent carbopol 940 was incorporated into emulsion to produce emulgel (i.e., standard conventional method). Results: The developed formulations were characterized using various parameters including particle size (PS), zeta potential (ZP), polydispersity index (PDI), entrapment efficacy (EE), pH, extrusion efficacy, physical stability, in-vitro drug release studies, and scanning electron microscopy (SEM). PS, EE, PDI, ZP and In-vitro studies ranges between 186.25 ± 6.42 mm (LE-F4) to 395.24 ± 8.64 mm (LE-F1), 62.38 ± 0.36 % (LE-F2) to 76.48 ± 0.69 % (LE-F4), 0.276 ± 0.02 (LE-F4) to 0.652 ± 0.02 (LE-F1), 16.45 ± 2.13 mV (LE-F1) to 29.46 ± 2.78 mV (LE-F3) and 21.90 ± 0.3 % (LE-F1) to 68.30±0.9 % (LE-F4) respectively. Conclusion: Based on all physicochemical properties, LE-F4 formulation was considered to be optimized with minimum PS (186.25±6.42 nm), PDI (0.276±0.02), satisfactory positive surface charge (23.15 ± 1.89 mV) and maximum EE (76.48±0.69 %). FTIR studies were confirmed that there is no physical interaction between drug and excipients and SEM studies revealed that vesicle size was spherical with smooth texture. A significantly greater rate of drug release (i.e., 68.30 ± 0.90%) was seen in the LTD emulgels that were made with cationic surfactant (i.e., LE-F4) and found to be good spreadability and extrudability.